IMPLEMENTASI HIKMAH PENDIDIKAN AKHLAK - Arisanti (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2016)
Morality is one of the popular topics in all media. Recently, we are shocked by sensational news about someone who is able to double money. That person is Dimas Kanjeng Taat Pribadi. This case drags an intellect Muslim, Marwah Daud who believes to Dimas kanjeng. It shows that our moral in Indonesia is decline, since religion is not considered as authentic information. This phenomenon implicates that the high intelligence of someone cannot balance her/his emotional. It shows that her intelligence is only tex-tual or physic form. In short, moral education is the best solution to make perfect generation. Moral is all the good and bad things which emerge from the soul without a thought and contemplation first. From this definition, it can be identified two morals; they are good and bad moral. The good moral can be gotten by beating out and observing command from Allah, and befriend with good people. Describing our prophet’s behavior, attitude, and good moral constitutes good relationship with the Creature. Since, basically moral education is not only related to attitude, but also related to belief.